LITERATUR REVIEW RECIRCULATING AQUACULTURE SYSTEM (RAS) BIOSTIMULAN ANALISIS KRITIS POTENSI SERTA TANTANGAN DALAM BUDIDAYA IKAN INTENSIF YANG BERKELANJUTAN - Yulius Kisworo (Chlorophyl, 2025)
The integration of Recirculating Aquaculture System (RAS) with biostimulant technology represents an innovative approach in sustainable aquaculture. This combined system facilitates efficient water usage, optimal environmental control, and enhanced productivity. This article presents a comprehensive literature review of various relevant sources, examining the working principles, key components, current applications in Indonesia, and the social approach to empowering disabled communities through this technology. The review findings indicate that the integration of RAS technology with biostimulants is not only technically effective but also yields positive socioeconomic impacts for vulnerable groups, particularly disabled communities. With proper management, this system holds promise as an adaptive and inclusive aquaculture model for the future